Ozone therapy as a treatment method for bovine mastitis – Literature review - Porn, Thuane de Aguiar; Chapel, Maria Eduarda Masello; Marins, Marcella Santos de; Tavares, Nathália de Almeida; Silva, Laís Siqueira Barboza da; Deboni, Ana Carolina do Nascimento; Pina, Eliene Porto Sad; Ferrer, Daniela Mello Vianna; Leite, Dala Kezen Vieira Hardman (Seven Editora, 2024)
Mastitis is a common disease in dairy farming worldwide, characterized by inflammation of the mammary gland, bringing economic losses to producers, due to the compromise in milk quality, reduction in the scale of production, treatment expenses, early disposal of animals, in addition to the disposal of milk during the grace period due to the use of antibiotics. Conventional treatment includes the use of antibiotic therapy, however, more recently, this treatment has been questioned, due to the presence of residues in milk and the risk that this milk can bring to consumers. Currently, ozone therapy is being used as a form of integrative treatment for several pathologies, demonstrating great efficacy for bovine mastitis. The studies and experiments already carried out with this gas show that this treatment method is promising for the producer, because it is a low-cost treatment and because it does not leave residues in the milk. However, it is a new treatment, which needs more studies regarding dosages, forms of application and correct treatment time so that it can generate more current scientific data. The objective of this article is to carry out a literature review in order to study the existing information on the use of ozone as a treatment method for bovine mastitis, as well as to know the therapeutic properties of ozone gas for this disease. The methodology was based on articles and other documents, such as books and technical bulletins, all focused on the use of ozone as a treatment for mastitis, using databases that are referenced in Google Scholar. In bovine mastitis, ozone therapy is a promising technique because it is a low-cost treatment when compared to antibiotic therapy. Finding an effective method for the prevention and treatment of mastitis has led researchers to advance in the studies of integrative treatment so that they can enjoy better productivity, improve the quality of milk products and their derivatives and avoid threats to human and animal health. DOI:https://doi.org/10.56238/sevened2024.007-071